Sperm swimming speed and morphology differ slightly among the three genetic morphs of ruff sandpiper (Calidris pugnax), but show no clear polymorphism - Bulla, Martin; Küpper, Clemens; Lank, David B.; Albrechtová, Jana; Loveland, Jasmine L.; Martin, Katrin; Teltscher, Kim; Cragnolini, Margherita; Lierz, Michael; Albrecht, Tomáš; Forstmeier, Wolfgang; Kempenaers, Bart (Frontiers in Ecology and Evolution, 2024)
The ruff sandpiper (Calidris pugnax) is a lekking shorebird with three male morphs that differ remarkably in behavior, ornaments, size, and endocrinology. The morphs are determined by an autosomal inversion. Aggressive Independents evolved first, female-mimicking Faeders ~4 mil year ago when a short segment of a chromosome reversed in orientation, and semi-cooperative Satellites ~70,000 years ago through a recombination of the Independent and Faeder inversion-segment genotypes. Although the genetic differences between the morphs affect numerous phenotypic traits, it is unknown whether they also affect sperm traits. Here, we use a captive-bred population of ruffs to compare ruff sperm to that of other birds and compare sperm swimming speed and morphology among the morphs. Ruff sperm resembled those of passerines, but moved differently. Faeder sperm moved the slowest and had the longest midpiece. Independents’ sperm were neither the fastest nor the least variable, but had the shortest tail and midpiece. Although the midpiece contains the energy-producing mitochondria, its length was not associated with sperm swimming speed. Instead, two of three velocity metrics weakly positively correlated with head length (absolute and relative). We conclude that there is an indication of quantitative differences in sperm between morphs, but no clear sperm polymorphism.